Private Forests in Nepal: Status and Policy Analysis - Amatya, Swoyambhu M.; Lamsal, Prakash (Journal of Forest and Livelihood, 2017)
This paper reviews and analyses the present status of private forests and tenure administration in light of existing legal, policy, and regulatory frameworks in Nepal. Additionally, the present status of private forests, as well as the scenarios of timber harvesting, transportation, marketing, and their administration are thoroughly revised. Provisions regarding forests and trees on private land and their basis are examined and implications are articulated for potential policy improvements for enhanced tenure security. It is shown that robust national-level policies and legal frameworks exist, and that there is an increasing trend of timber flows to markets from private forests over the past five years. However, there is still skepticism, mistrust and fear amongst private forest owners, saw millers, and forest administration that prevents the full use of the bundle of rights that legal and policy provisions have promised. An unusually slow pace of private forest registration, lengthy and multi stage processes for obtaining harvesting and transportation permits, and official bans on important commercial species, among others, are found to be the factors that most hinder the private forest owners’ and tree growers’ interests, and their rights and obligations with respect to the management and use of their private forest resources. It is concluded that a simplified permitting process along with programmatic support would promote and help to grow private forestry and that Nepal’s experience and lessons learned from community forest implementation would be a great asset to move towards this end. Connecting community forest user groups for organised and cooperative action, and mobilising their institutional strength and accumulated funds for pro-farmer technical and regulatory support would allow farmers to intensify tree plantations and forest management. Further steps are required to convince policymakers and secure necessary budgetary support to this end..